The Effect of Self Efficacy and Locus of Control on Job Performance Conec World Surabaya Startup Employee - Nilla Tazkia Jumaharta; Sulastri Irbayuni (PT FORMOSA CENDEKIA GLOBAL, 2023)
The emergence of dynamic problems in the field of Human Resources (HR) in most startup companies in Indonesia resulted in a decrease in employee Job Performance. One of them is the decrease in job Performance of employees in startup companies ConecWorld Surabaya, which in fact Job Performance is one of the most important instruments in the process of achieving a company's goals, therefore the factors in it are very interesting to study. This study aims to determine the effect of Self-Efficacy and Locus of Control on Job Performance of employees of Startup companies ConecWorld Surabaya. This study was conducted at the Startup company ConecWorld Surabaya with a total population and a sample of 50 employees. Data from this study is the primary data obtained through the interview method, the dissemination of questionnaires and observations. The method of data analysis in this study using SEM (Structural Equation modeling) with the analysis tool PLS (Partial Least Square). The results of this study show that both Self-Efficacy and Locus of Control are able to support the improvement of employee Job performance, evidenced by the higher level of Self-Efficacy and the ability of Locus of Control that exist in employees, it can improve the Job Performance of conecworld Surabaya startup employees.